Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1093/ajcn/86.4.1167
|View full text |Cite
|
Sign up to set email alerts
|

Serum zinc and pneumonia in nursing home elderly

Abstract: Normal serum zinc concentrations in nursing home elderly are associated with a decreased incidence and duration of pneumonia, a decreased number of new antibiotic prescriptions, and a decrease in the days of antibiotic use. Zinc supplementation to maintain normal serum zinc concentrations in the elderly may help reduce the incidence of pneumonia and associated morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 43 publications
4
88
2
3
Order By: Relevance
“…Zinc supplementation reduces both the risk and duration of pneumonia in children and is also beneficial in the management of infantile diarrhea [10,12,81]. Zinc supplementation to maintain a normal serum concentration may help to reduce the mean incidence of infections (i.e., common cold, cold sores and flu) [81] as well as the incidence of pneumonia and associated morbidity in the elderly [82]. It has been reported that adequate zinc supply could prevent age-related diseases in the elderly such as cancer, atherosclerosis, dementia, Alzheimer's disease, etc.…”
Section: Immune Function and Upper Respiratory Tract Infectionsmentioning
confidence: 99%
“…Zinc supplementation reduces both the risk and duration of pneumonia in children and is also beneficial in the management of infantile diarrhea [10,12,81]. Zinc supplementation to maintain a normal serum concentration may help to reduce the mean incidence of infections (i.e., common cold, cold sores and flu) [81] as well as the incidence of pneumonia and associated morbidity in the elderly [82]. It has been reported that adequate zinc supply could prevent age-related diseases in the elderly such as cancer, atherosclerosis, dementia, Alzheimer's disease, etc.…”
Section: Immune Function and Upper Respiratory Tract Infectionsmentioning
confidence: 99%
“…La suplementación con zinc puede reducir el estrés oxidativo, la inflamación y la incidencia de infección (122)(123)(124). Se ha propuesto el zinc para competir con metales prooxidantes, evitando así la formación de radicales libres (125,126).…”
Section: Zincunclassified
“…Previously, we showed that a high proportion of nursing home elderly (w30%) had low serum zinc concentrations at baseline and after 1 y of follow-up (4). In that study, we observed that elderly patients with low serum zinc concentrations (,70 mg/dL) had a significantly higher incidence and longer duration of pneumonia, as well as all-cause mortality, than did those with adequate serum zinc concentrations ($70 mg/dL) (4).…”
Section: Introductionmentioning
confidence: 96%